COVID-19-Associated Mortality among Kidney Transplant Recipients and Candidates in the United States - Mohan, Sumit; King, Kristen L; Husain, S Ali; Schold, Jesse D (Clinical journal of the American Society of Nephrology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has had a profound effect on transplantation activity in the United States and globally. Several single-center reports suggest higher morbidity and mortality among candidates waitlisted for a kidney transplant and recipients of a kidney transplant. We aim to describe 2020 mortality patterns during the COVID-19 pandemic in the United States among kidney transplant candidates and recipients. Using national registry data for waitlisted candidates and kidney transplant recipients collected through April 23, 2021, we report demographic and clinical factors associated with COVID-19-related mortality in 2020, other deaths in 2020, and deaths in 2019 among waitlisted candidates and transplant recipients. We quantify excess all-cause deaths among candidate and recipient populations in 2020 and deaths directly attributed to COVID-19 in relation to prepandemic mortality patterns in 2019 and 2018. Among deaths of patients who were waitlisted in 2020, 11% were attributed to COVID-19, and these candidates were more likely to be male, obese, and belong to a racial/ethnic minority group. Nearly one in six deaths (16%) among active transplant recipients in the United States in 2020 was attributed to COVID-19. Recipients who died of COVID-19 were younger, more likely to be obese, had lower educational attainment, and were more likely to belong to racial/ethnic minority groups than those who died of other causes in 2020 or 2019. We found higher overall mortality in 2020 among waitlisted candidates (24%) than among kidney transplant recipients (20%) compared with 2019. Our analysis demonstrates higher rates of mortality associated with COVID-19 among waitlisted candidates and kidney transplant recipients in the United States in 2020.